2015
DOI: 10.17583/ijep.2015.1769
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Educational Psychology in an Emerging Democracy

Abstract: <p>This paper reflects on the changes in Educational Psychology in South Africa in a ten year period (2005 – 2015) after the first democratic elections.  It shows how Educational Psychology as a scientific discipline, and as a helping profession, has responded to the changing landscape and how the post-democracy years inspired a complete departure from previous practices.  It also explores an expansion of its leitmotif from ‘helping’ to leading and facilitating processes of change and support.  It shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Educational psychology, a psychology discipline that specialises in learning and education, focuses (among others) on theories of learning, human development, behaviour, socioemotional development and cognition-all of which are keys to education systems. In South Africa, educational psychology was initially seen as a helping and intervention profession [17,18]. Teachers as subject specialists who rely on psychological theories to understand learning and teaching requirements per grade and developmental phase.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational psychology, a psychology discipline that specialises in learning and education, focuses (among others) on theories of learning, human development, behaviour, socioemotional development and cognition-all of which are keys to education systems. In South Africa, educational psychology was initially seen as a helping and intervention profession [17,18]. Teachers as subject specialists who rely on psychological theories to understand learning and teaching requirements per grade and developmental phase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These challenges, which are still relevant today, include communicating the relevance of educational psychology in education, developing collaborative relationships with colleagues in education programmes, and documenting ways that educational psychology courses can make a difference in the practice of teachers [10] (p. 71). The author of [17] looked at the changes and developments of educational psychology in South Africa since 1994 and suggested that knowledge of developmental theories and how they influence the education system is insufficient in teacher education. Further research is needed to understand the role and contribution of educational psychology in teacher education and learner support.…”
Section: Introductionmentioning
confidence: 99%